Sugar taxes: An economy-wide assessment: The case of Guatemala - Piñeiro, Valeria; Díaz-Bonilla, Eugenio; Paz, Florencia; Allen, Summer L. (International Food Policy Research Institute, 2019)
This study presents an economy-wide analysis for Guatemala, considering several tax options on sugar and SSB and then tracing their differentiated general economic effects. We focus on Guatemala, considering the increasing health burden imposed by obesity and the fact that it is also an important sugar producer and exporter. In the next section we describe the general conditions for sugar production and consumption in Guatemala. We then describe the economy-wide model utilized, the modeled scenarios, and finally, the results of the simulations before concluding.